High-resolution Observations of Pickup-ion-mediated Shocks to 60 au - Bishwas L. Shrestha; David J. McComas; Eric J. Zirnstein; George Livadiotis; Heather A. Elliott; Pontus C. Brandt; Alan Stern; Andrew R. Poppe; Joel Parker; Elena Provornikova; Kelsi Singer; Anne Verbiscer; et al. (The Astrophysical Journal)
This study provides a detailed analysis of 14 distant interplanetary shocks observed by the Solar Wind Around Pluto instrument on board New Horizons. These shocks were observed with a pickup ion data cadence of approximately 30 minutes, covering a heliocentric distance range of ∼52–60 au. All the shocks observed within this distance range are fast forward shocks, and the shock compression ratios vary between ∼1.2 and 1.9. The shock transition scales are generally narrow, and the SW density compressions are more pronounced compared to the previous study of seven shocks by D. J. McComas et al. A majority (64%) of these shocks have upstream sonic Mach numbers greater than 1. In addition, all high-resolution measurements of distant interplanetary shocks analyzed here show that the shock transition scale is independent of the shock compression ratio. However, the shock transition scale is strongly anticorrelated with the shock speed in the upstream plasma frame, meaning faster shocks generally yield sharper transitions.